Research opportunities at the geospace facilities exemplified by a large meteor echo - Hysell, D. L.; Kirchman, A.; Vega, G.; Chau, J. L. (Frontiers in Astronomy and Space Sciences, 2026)
A small 30-MHz coherent scatter radar imager has been deployed to the HAARP facility near Gakona, Alaska, for studying the effects of ionospheric modifications on polar mesospheric summer echoes (PMSEs). In initial tests scheduled during the 2025 Perseids shower, the radar observed a remarkably long-lived non-specular meteor trail. Although not optimized for the purpose, the radar mode used was sufficiently general to permit analysis of the echoes. This paper explores the results of the analysis and highlights the adjacent science that can be performed in the backdrop of multi-purpose geospace research facilities like HAARP. Lessons learned from the exercise and perspectives on the role and value of the geospace facilities are discussed.